Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1042/bsr20201545
|View full text |Cite
|
Sign up to set email alerts
|

miR-200-3p suppresses cell proliferation and reduces apoptosis in diabetic retinopathy via blocking the TGF-β2/Smad pathway

Abstract: Increasing evidence has shown that microRNAs (miRNAs) play an important role in the pathogenesis of diabetic retinopathy (DR). However, the role and mechanism of miRNA in regulating high glucose (HG)-induced ARPE-19 cell injury are still not well understood. This study aimed to investigate the effects of miR-200a-3p on DR progression and reveal the underlying mechanisms of their effects. In the present study, we observed that miR-200a-3p was significantly decreased, while transforming growth factor-β2 (TGF-β2)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 38 publications
2
14
0
Order By: Relevance
“…These results suggested that overproliferation of RECs and retinal angiogenesis was mainly driven by high glucose rather than high osmotic pressure (26). Meanwhile, high glucose remarkably induced an increase in expressions of TGF-β1 and VEGF, and decreased expression of miR-200b in RECs, which was similar to the results in previous studies (27). However, after miR-200b mimic was transfected into RECs under high glucose condition, TGF-β1 level was also signi cantly elevated.…”
Section: Discussionsupporting
confidence: 88%
“…These results suggested that overproliferation of RECs and retinal angiogenesis was mainly driven by high glucose rather than high osmotic pressure (26). Meanwhile, high glucose remarkably induced an increase in expressions of TGF-β1 and VEGF, and decreased expression of miR-200b in RECs, which was similar to the results in previous studies (27). However, after miR-200b mimic was transfected into RECs under high glucose condition, TGF-β1 level was also signi cantly elevated.…”
Section: Discussionsupporting
confidence: 88%
“…In the eye, many miRNAs have been found to be abundantly expressed and play important roles in ocular physiology and pathology. These include miR-200 [ 64 ] miR-184 [ 65 ] miR-29 family [ 66 ] and miR-21 [ 67 ]. Expression profiling of miRNAs in the anterior segment of healthy donors including cornea, TM, and ciliary body samples reported 378 miRs collectively expressed [ 68 ].…”
Section: Micrornas That Regulate Tgf-β Signallingmentioning
confidence: 99%
“…These cells were initially transfected for 6 h and then the medium was replaced with DMEM/ f-12 medium containing 30 mM high glucose (HG). After 24-h incubation, the cells were subjected to the following experiments [ 23 ].…”
Section: Methodsmentioning
confidence: 99%